Sensory Quality Analysis and Business Feasibility Study of Coffee (Coffea) and Noni (Morinda citrofolia) Syrup as an Alternative to Functional Drinks - Yoga Aprilia Suganda; Hesti Nur'aini; Methatias Ayu Moulina (SINTA Journal (Science, Technology, and Agricultural), 2021)
Coffee has enormous potential to be developed into a food product. In addition, noni fruit as a local Indonesian fruit also has the potential as a source of functional food. Research has been carried out with the aim of analyzing the sensory quality and business feasibility of coffee syrup substituted with noni fruit. The study used a factorial design with 1 (one) treatment factor, namely variations in the composition of coffee and noni ((100; 0); (95: 5); (90:10); (85:15); (80:20)). The analysis carried out included analysis of yield, viscosity, sensory test and business feasibility of noni coffee syrup. The results showed that the less coffee used, the lower the yield, viscosity and the panelists' preference for syrup, with the best treatment being 85 grams of coffee and 15 grams of noni, with the panelist's preference for color 3.46 (like) , aroma 3.40 (like) and taste 3.51 (like), and yield 78.05 and viscosity 114.70 cp. The feasibility analysis of the noni coffee syrup business shows that the noni coffee syrup with a treatment of 85 grams of coffee and 15 grams of noni produces an r / c ratio of 1.3, so this business is feasible to develop